Impact of inoculum acclimation on energy recovery and investigation of microbial community changes during anaerobic digestion of the chicken manure. Issue 1 (2nd January 2020) - Yangin-Gomec, Cigdem; Sapmaz, Tugba; Aydin, Sevcan
ABSTRACT: The aim of this study was to assess the effect of inoculum adaptation on biogas recovery from two identical lab-scale semi-continuous anaerobic digesters (AD) treating chicken waste (i.e. TS and VS contents of ca. 6.2% and 2.9%, respectively) at mesophilic condition (35°C). For the first two months; one of the AD was run with adapted whereas the second AD was run with unadapted granular sludge to chicken manure which was further operated for about 100 more days. In this scope, qPCR analysis and Illumina sequencing were also used to detect microbial community changes inside anaerobic reactors. Molecular analyses revealed that the number of archaea was significantly higher than that of overall archaea compared to the values obtained at the start-up time and methanogens also increased as the operation continued. On the other hand, although average daily biogas production was about 25% higher in adapted AD compared to the unadapted AD (i.e. biogas yields were ca. 0.6 and 0.7 m 3 /kg VSfeed, respectively), there was not a meaningful change in archaea numbers at the end of the operation. These suggest that changes in the structure of a microbial community lead to changes in biogas production and controlling ultimate methanogenic archaeal community may promote successful methane production in anaerobic reactors. GRAPHICAL ABSTRACT: